How to manage your priorities - Chan, Janis Fisher (American Management Association, 2007)
The latest tools and techniques for accomplishing more in less time with fewer resources. In today's competitive global environment-where people at all levels need to accomplish more, in less time, with fewer resources-the ability to manage priorities is a key element in personal and professional success. How to Manage Your Priorities, Second Edition, provides managers, team leaders, professionals, and others in the workplace with the tools to master this essential business skill. The second edition, revised and updated with a new chapter on technology-based tools for identifying and organizing priorities, teaches managers the critical benefits of managing their priorities and removing the obstacles that interfere with success. Readers will learn how to: Identify what's important Accomplish more in less time, with fewer resources Manage your workload to improve your working relationships Organize a task or project so outcomes meet expectations and objectives Collaborate with others to make sure deadlines are necessary and reasonable Improve the quality of your work and reduce stress Master key strategies for prioritizing tasks and activities Practice the best planning and scheduling techniques Use technology to manage your priorities: planning and scheduling tools, project management software, PDAs, organizing systems. This is an ebook version of the AMA Self-Study course. If you want to take the course for credit you need to either purchase a hard copy of the course through amaselfstudy.org or purchase an online version of the course through www.flexstudy.com.